Experience of Nursing Student during Geriatric Nursing Practice: A Narrative Qualitative Study - Saputri, Agustina; Lumbantoruan, Septa Meriana (STIKep PPNI Jawa Barat, 2024)
Aims: Older adults are often accompanied by chronic disease which makes nursing care more complex. The experiences of students providing care to older adults can encourage them to gain a deeper understanding, find effective strategies when facing challenges, and realize their own needs as future nurses. This study aimed to determine the experiences of nursing students in carrying out geriatric nursing practice. Methods: This study employed a qualitative study using a narrative research design. The purposive sample consisted of twelve nursing students who had completed 2 weeks of geriatric nursing. The variables explored were experiences of nursing students during geriatric nursing practice. Data collection used in this study was a student’s reflective assignment. The analysis was conducted using a thematic analysis approach. Results: All respondents were willing to participate in the study. Five themes emerged, including family assistance during care, the patient's condition while undergoing treatment, students' feelings and competencies when caring for the elderly, changes in a better understanding of the elderly, and expected goals to be achieved by students. Conclusions: This study focuses on the implementation of care for elderly patients in the hospital, which promotes the need for students to improve their skills in providing nursing care.